Evidence for oxylipin synthesis and induction of a new polyunsaturated fatty acid hydroxylase activity in Chondrus crispus in response to methyljasmonate - Gaquerel, Emmanuel (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2006)
Signaling cascades involving oxygenated derivatives (oxylipins) of polyunsaturated fatty acids (PUFAs) are known to operate in response to external stimuli. The marine red alga Chondrus crispus uses both oxygenated derivatives of C18 (octadecanoids) and C20 (eicosanoids) PUFAs as developmental or defense hormones. The present study demonstrates that methyljasmonate (MeJA) triggers a cascade of oxidation of PUFAs leading to the synthesis of prostaglandins and other oxygenated fatty acids. As a result of a lipoxygenase-like activation, MeJA induces a concomitant accumulation of 13-hydroxy-9Z,11E-octadecadienoic acid (13-HODE) and 13-oxo-9Z,11E-octadecadienoic acid (13-oxo-ODE) in a dose-dependent manner in C. crispus. Furthermore, MeJA increases the level of mRNA encoding a gluthatione S-transferase and induces the activity of a new enzyme catalyzing the regio- and stereoselective bisallylic hydroxylation of polyunsaturated fatty acids from C18 to C22. The enzyme selectively oxidized the omega minus 7 carbon position (ω-7) and generated the stereoselective (R)-hydroxylated metabolites with a large enantiomeric excess. The enzyme specificity for the fatty acid recognition was not dependent of the position of double bonds but at least requires a methylene interrupted double bond 1,4-pentadiene motif involving the ω-7 carbon.